Disparity in Post-Disaster Response and Recovery: A Study on the Funding of the Mount Lewotobi Laki-Laki Eruption in East Flores - Patricia, Angel; Pandie, David B.W.; I Putu Yoga Bumi Pradana (Catalist Indo Publisher, 2025)
Background This study examines the imbalance between emergency response funding and long-term recovery financing following the 2024 eruption of Mount Lewotobi Laki-Laki in East Flores. The research aims to determine whether the global pattern, marked by rapid and substantial funding during the response phase and a sharp decline during recovery, also appears in this local context. Methods A qualitative approach was employed by combining a systematic review of disaster-financing literature in Asia with empirical data from East Flores. Data were collected through document analysis, official reports, and in-depth interviews with humanitarian practitioners and local authorities. Thematic coding was used to analyze patterns in funding flows, institutional constraints, and community experiences. Results Findings reveal a structural gap between response and recovery funding. Support during the emergency phase was abundant, while recovery efforts faced limited and inconsistent financial resources. This shortfall contributed to delays in permanent housing, unclear relocation processes, disrupted education services, loss of livelihoods, and heightened social and psychological stress among affected communities. Conclusions The study highlights the need for long-term recovery funding schemes, stronger coordination mechanisms, and greater community involvement in recovery planning. These insights underscore the importance of improving disaster-recovery governance in low-fiscal island regions such as Eastern Indonesia.